Money and electoral politics local parties and funding at general elections - Johnston, Ron 1941-2020; Pattie, Charles J. 1962- (Policy Press, 2014)
In this book, the authors use the latest research to explore financial differences across the UK's three main parties in the four years leading up to the 2010 General Election, revealing an unhealthy picture of grassroots party organisation in which the capacity to engage with many voters is concentrated in a few constituencies